Factors Behind the Occurrence of Code Mix in the Daily Conversation of Santriwati SMK Entrepreneur Indonesia Sragen - Hanik, Khalifah Umi; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The objective of this study is to describe the forms of code mixing used in daily conversation and to identify the factors that cause code mixing in the daily conversations of students at SMK Entrepreneur Indonesia Sragen. Methodology: This research uses a descriptive qualitative approach with students’ speech as the data source. Data were collected through free listening, note-taking, recording, interviews, and observation techniques. Results: The results show that forms of code mixing found include words, phrases, baster, and clauses in Javanese, Arabic, and English, which are inserted into Indonesian speech. Three factors were identified as the causes of code mixing: casual and informal situations, environmental influences, and the use of more popular terms. Applications/Originality/Value: The application or authenticity of this research lies in providing insights into the forms and causes of code mixing that occur naturally in students’ daily conversations, which can be used as a reference for further sociolinguistic studies or to develop teaching strategies that address bilingual or multilingual contexts in schools.